Denotational Associations between Architecture and Music: A Reflection on Commonalities of Iranian Architecture and Music - Farhad Shariatrad (صفه)
Music is an abstract art which tries to make connections with the world of meanings, and architecture is an applied one, which can respond to mental requirements and convey transcendental thoughts on top of responding to physical needs. They share formal denotational aspects, whether qualitative or quantitative, and many have attempted to associate the two by drawing parallels between architectural and musical works, both structurally and conceptually, and to a lesser extent, by finding common purposes between them. Trying to introduce commonalities between architecture and music,with reference to the features of Iranian architecture and music, the present paper tries to focus on their qualitative aspects. Besides theoretical debates regarding commonalities and differences between architecture and music, it seems that many audiences have had personal experiences of finding modal similarities Iranian architecture and music. The question is, therefore, that of formal and denotational commonalities between the two artforms, namely, which Iranian architecture factors make it coherent with Iranian music in the audience’s mind? To answer, it is necessary to start with recognising the two artforms’ characteristics, particularly in their Iranian versions. This is continued with a closer scrutiny in order to extract common qualities using a hermeneutic approach. In conclusion some factors are introduced, which can be used to understand commonalities between the two, recognising that the appreciation of these commonalities might differ from one person to the other.